Serological and biological variations of African cassava mosaic virus in Nigeria - Ogbe, F.O.; Atiri, G.I.; Dixon, Alfred G.O.; Thottappilly, G. (Wiley, 2003)
To determine the occurrence of variants of African cassava mosaic virus, 316 cassava leaf samples were collected from mosaic-affected cassava plants in 254 farmers. fields in 1997 and 1998, covering the humid forest, coastal/derived, southern Guinea and northern Guinea savannas and arid and semi-arid agroecologies of Nigeria. The samples were tested in triple antibody sandwich enzyme-linked immunosorbent assay using a panel of 10 monoclonal antibodies (MAbs) against the virus in which 29 reaction patterns were observed. In cluster analysis, nine serotypes were obtained at 0.80 Jaccard similarity coefficient index in which at least 50% of isolates of each serotype reacted alike. The serotypes ranged between two extremes: serotype 1 with 90% isolates reacting with the 10 MAbs and serotype 8 in which 90% of its isolates failed to react with the antibodies. Isolates of serotypes 1, 2, 4 and 8 were widely distributed while those of the other serotypes were estricted to certain agroecologies. Four representative isolates 227 (serotype 1), 231 (serotype 2), 235 and 283 (serotype 8) elicited different responses in Nicotiana, benthamiana, with isolate 283 not able to infect this and other test plants used. The serological variations did not necessarily reflect the biological variations. In polymerase chain reaction tests, one out of the five pairs of ACMV primers tested distinguished only isolate 283. The humid forest, derived/coastal and southern Guinea savannas where most of the crop is grown in Nigeria had a high number of variants, which makes the agroecologies suitable for the selection of resistant cassava clones against ACMV.